A group decision-making tool for the application of membrane technologies in different water reuse scenarios - Sadr, S.M.K.; Saroj, D.P.; Kouchaki, S.; Ilemobade, A.A.; Ouki, S.K. (Journal of environmental management, 2015)
A global challenge of increasing concern is diminishing fresh water resources. A growing practice in many communities to supplement diminishing fresh water availability has been the reuse of water. Novel methods of treating polluted waters, such as membrane assisted technologies, have recently been developed and successfully implemented in many places. Given the diversity of membrane assisted technologies available, the current challenge is how to select a reliable alternative among numerous technologies for appropriate water reuse. In this research, a fuzzy logic based multi-criteria, group decision making tool has been developed. This tool has been employed in the selection of appropriate membrane treatment technologies for several non-potable and potable reuse scenarios. Robust criteria, covering technical, environmental, economic and socio-cultural aspects, were selected, while 10 different membrane assisted technologies were assessed in the tool. The results show this approach capable of facilitating systematic and rigorous analysis in the comparison and selection of membrane assisted technologies for advanced wastewater treatment and reuse. [Display omitted] •Proposed framework provides a robust tool for assessing water reuse technologies.•Results from the tool coincide with the existing water reuse case studies.•Presence of NF/RO would play a major role in potable water reuse applications.•Results show that the cost and energy were high in non-potable reuse scenarios.